Traditional Game Module Development: An Alternative To Stimulate Early Childhood Language Development - Rahnang Rahnang; Farninda Aditya; Merna Merna; Lidya Lidya (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
This research produced a product in the form of a traditional West Kalimantan game book. The research that will be carried out using Research & Development (R & D) research for west Kalimantan traditional game resources the author obtained through observation and interviews as well as documentation as data analysis and data reinforcement as well as evidence of the implementation of research activities. Meanwhile, the locus of this study was conducted in the Coastal area of West Kalimantan, which focused on Tanjung Satai Village, Pulau Maya District, North Kayong Regency. This coastal area refers to the village area located on the island surrounded by the sea, namely the Karimata Strait. This research shows that the results of West Kalimantan traditional games, especially Mimi and Kotaplus, are able to stimulate the development of early childhood language aged 6 to 6 years. In addition, the presence of hand movements in the game stimulates the physical-motor and cognitive development of the child.